The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.ypmed.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Nine year changes in sitting time in young and mid-aged Australian women: Findings from the Australian Longitudinal Study for Women's Health

Abstract: Word count abstract: 200 Word count main text: 2 769 Highlights• Over nine years sitting time (ST) decreased in young women and increased in midaged women.• Decreased ST was associated with having a baby, beginning work and decreased income in young women.• Decreased ST was associated with retirement and decreased income in mid-aged women. 2• Increased ST was associated with returning to study and job loss in young women.• Increased ST was associated with changes at work in mid-aged women. Results Against a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…O’Donoghue et al [25] systematically reviewed 74 studies on correlates of sedentary behavior, yet only 8 studies reported on the presence of children in the household. Five of these studies found lower overall sitting times among people who have children [26,27,28,29,30]; however, two reported higher sitting times while commuting [27,31]. Busschaert et al [32] found that adults with children sat 21% less while using a home computer.…”
Section: Discussionmentioning
confidence: 99%
“…O’Donoghue et al [25] systematically reviewed 74 studies on correlates of sedentary behavior, yet only 8 studies reported on the presence of children in the household. Five of these studies found lower overall sitting times among people who have children [26,27,28,29,30]; however, two reported higher sitting times while commuting [27,31]. Busschaert et al [32] found that adults with children sat 21% less while using a home computer.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in sitting time for transportation and work over the 6-year period were only observed in women. Other self-report research with Australian mid-aged women has found that an increase in overall sitting time was associated with "changes at work", which were discussed as potentially reflecting increasing (sedentary) seniority and managerial responsibilities and subsequently more desk based work [25). Increased occupational sitting time may also reflect more mid-aged women returning to the workforce: Australian workforce data indicate a marked increase in women aged 55-59 in employment during the past decade, from 50% in 2005 to 64% in 2016 [13].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Furthermore, few longitudinal studies have revealed the patterns and predictors of sitting time throughout adulthood, suggesting that several factors and life events (eg, male gender, higher education, full‐time employment, staying obese, and consistently low physical activity levels, and changing jobs, retiring, or illness) contribute to high sitting levels. Divergent associations were identified for different aged groups for women . In all of these studies, both total and prolonged sitting time were limited using subjective classification analysis, and the sample included participants with a wide range of ages.…”
Section: Introductionmentioning
confidence: 99%
“…Divergent associations were identified for different aged groups for women. 25 In all of these studies, both total and prolonged sitting time were limited using subjective classification analysis, and the sample included participants with a wide range of ages. However, no studies have focused specifically on whether changes in TV-time would be substantially limited by long-term sociodemographic and health factors.…”
Section: Introductionmentioning
confidence: 99%